Redefining Islamic Da’wah through Generation Z’s Digital Engagement in Indonesia - Masripah (Sinergi International Journal of Islamic Studies, 2023)
This study investigates the transformative role of Generation Z in Indonesia’s digital Islamic da’wah landscape, focusing on their active participation as both content consumers and creators. As digital natives, Gen Z increasingly utilizes platforms such as TikTok, Instagram, and Canva to design and disseminate religious messages, redefining traditional clerical models of Islamic preaching. Employing qualitative methods, including digital ethnography, semi-structured interviews, and content analysis, this research analyzes how youth reinterpret Islamic teachings in visually engaging and culturally resonant formats. The study examined their platform preferences, creative strategies, and challenges faced in balancing aesthetic appeal with theological depth. Findings indicate that Gen Z’s use of visual storytelling significantly enhances outreach and engagement, but also introduces tensions regarding misinformation, content saturation, and perceived religious authority. Student creators prioritize relatability and visual design, which often necessitate navigating trade-offs between popularity and substance. Institutional responses have begun to include media literacy initiatives and collaborations with digital influencers, aiming to ensure doctrinal accuracy while expanding reach. This research concludes that Gen Z’s integration of technology and religion signals a new era of decentralized, participatory da’wah. Their role extends beyond adaptation they are actively reshaping the meaning, delivery, and reception of Islamic messages. The study contributes to interdisciplinary dialogues in religious communication, youth culture, and digital media studies by emphasizing the pedagogical and institutional implications of youth-led digital da’wah.